Analysis of particles size distribution on the agglomeration and shrinkage of Alumina-Zirconia compacts - Afuza, A. A. (Universiti Malaysia Perlis (UniMAP), 2020)
Link to publisher's homepage at http://ijneam.unimap.edu.my